Human Friendly Robotics 10th International Workshop - Ficuciello, Fanny; Ruggiero, Fabio; Finzi, Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The International Workshop on Human-Friendly Robotics (HFR) is an annual meeting that brings together academic scientists, researchers and research scholars to exchange and share their experiences and research results on all aspects related to the introduction of robots into everyday life. HFR collects contributions on current developments of a new generation of human-friendly robots, i.e., safe and dependable machines, operating in the close vicinity to humans or directly interacting with them in a wide range of domains. The papers contained in the book describe the newest and most original achievements in the field of human-robot-interaction coming from the work and ideas of young researchers. The contributions cover a wide range of topics related to human-robot interaction, both physical and cognitive, including theories, methodologies, technologies, empirical and experimental studies.
Robot Control and Manipulation -- Natural Human-Robot Interaction -- Human robot collaboration -- Robot Learning.
Keywords: Control engineering; Robotics; Automation; Computational intelligence; Artificial intelligence; Control, Robotics, Automation; Computational Intelligence; Artificial Intelligence